Conditions and from factor of the five threatened fishes from the Jamuna (Brahmaputra River Distributary) River, Northern Bangladesah - Md. Yeamin Hossain,; Jun Ohtomi,; Md. Mosaddequr Rahman,; Md. Abu Sayed Jewel,; Zoarder Faruque Ahmed,; Ferdous Ahamed,; Bernerd Fulanda,; Elgorban M. Abdullah, (Universiti Kebangsaan Malaysia, 2012)
The small indigenous species namely Ailiichthys punctata (Day 1871), Botia lohachata (Chaudhuri 1912), Chanda nama (Hamilton 1822), Laubuca laubuca (Hamilton 1822) and Mystus cavasius (Hamilton 1822) comprise an important component of riverine fisheries of Bangladesh. But the natural populations are decreasing fast due to high fishing pressure as well as environmental degradation. Therefore, data and information is needed to avert the alarming decline and initiate conservation measures for these important fishes of the Jamuna River. This study describes the condition- (Fulton’s and Relative weight) and form-factor (a3.0) of the five threatened fishes from the Jamuna River, a distributary of the Brahmaputra River in northern Bangladesh. A total of 919 specimens from five species in five families used for this study were caught by traditional fishing gear during March 2010 through February 2011. For each individual, the total (TL), fork (FL) and standard (SL) length were measured by digital slide calipers while individual body weight (BW) was measured using a digital balance. The Fulton’s condition factor (KF) showed significant variations (p<0.01) among species, with best performance by B. lohachata (1.49±0.20) followed by C. nama(1.41±0.19), M. cavasius (0.79±0.14), L. laubuca (0.78±0.09) and A. punctata (0.71±0.12). The calculated minimum and maximum relative weight (WR) was 53.14 for C. nama and 167.88 for A. punctata, respectively. However, the estimated relative weight (WR) was close to 100 for all populations (p>0.05) indicating a balanced habitat with food availability relative to the presence of predators. The calculated minimum and maximum form factor (a3.0) was 0.0062 for A. punctata and 0.0158 for B. lohachata, respectively. To the best of our knowledge, this study presents the first reference on KF, WR and a3.0 factors for these threatened species in Bangladesh. The results would be useful for sustainable management and conservation of the limited stocks in the Brahmaputra River ecosystem